Commutative Pseudo Valuations on BCK-Algebras - Myung Im Doh; Min Su Kang (International Journal of Mathematics and Mathematical Sciences)
The notion of a commutative pseudo valuation on a BCK-algebra is introduced, and its characterizations are investigated. The relationship between a pseudo valuation and a commutative pseudo-valuation is examined.